The Impact of Entrepreneurial Passion on Psychology and Behavior of Entrepreneurs - Feng, Bing; Chen, Min (Frontiers in Psychology, 2020)
In order to study the influence of entrepreneurial passion on entrepreneurs’ psychology and behavior, based on the theory of self-efficacy, a model of relationship between entrepreneurial passion and entrepreneurs’ psychology and behavior was constructed, relevant hypotheses were proposed, and the promotion mechanism of entrepreneurial passion on entrepreneurial behavior and enterprise performance was analyzed. A survey of 300 entrepreneurs from Hangzhou, Wenzhou, Jiaxing, Shaoxing, and Huzhou was conducted to verify the reliability of the questionnaire through statistical description and analysis. Then exploratory factor analysis and confirmatory factor analysis were conducted to test the correlation between variables. Finally, the structural equation was simulated to verify the correctness of the proposed hypothesis and model. The results show that the designed questionnaire has good reliability (the correction item total correlation coefficients (CITC) of all scales are greater than 0. 3, values of Cronbach’s α are higher than 0. 6), the validity (all inventory accumulation explanation degree are higher than 50%) and the fitting (χ2/df values of all scales are less than 3, CFI, GFI, and IFI are greater than 0. 9, RMSEA value is less than 0. 08). The direct effect of harmonious passion on entrepreneurial persistence and enterprise performance is not significant, while the direct effect of compulsive passion on entrepreneurial persistence and enterprise performance is significant. Harmonious passion (P<0. 001) and compulsive passion (P<0. 01) are significantly correlated with entrepreneurial self-efficacy, and self-efficacy plays a mediating role between entrepreneurial passion and entrepreneur psychology and behavior (P< 0. 05), and the hypothesis proposed is basically valid. Therefore, entrepreneurial passion can positively guide the entrepreneurial persistence of entrepreneurs, and at the same time promote the performance of enterprises by stimulating the positive emotions of entrepreneurs. In addition, entrepreneurs can enhance their entrepreneurial role identity, maintain a positive attitude, stimulate creativity and innovation, to enhance their sense of energy efficiency. The government can also promote successful business cases to build an inclusive and innovative social environment and stimulate the entrepreneurial passion of entrepreneurs.